Consumer Purchase Decision on Fresh Fish in New Normal: Preliminary Case Study in Indonesia - farradia, yuary; Sunarno, Mas Tri Djoko (Journal of Social Transformation and Regional Development, 2020)
Indonesia scores among the top five of fishery and aquaculture producers in the world, therefore the Ministry of Marine Affair and Fisheries has expected the aquaculture to play an increasingly important role in economic development and food security for the country. Covid-19 pandemic has an impact on the aquaculture industry in particular fresh water aquaculture subject to its consumer behavior pattern toward online purchase. There are an indication that online purchase become a preferred choice in the new normal era. This paper studied on factors affecting consumer behavior pattern of fresh fish online purchase decision in new normal subject to Covid 19 pandemic in Indonesia based on consumer buying decision variables namely culture, social, personal and psychological. A multiple regression analysis was used to run the data from 107 respondents who prefer to buy online in Indonesia. The result indicated a new trend of consumer behavior pattern to buy fresh fish on line instead of going to the market. Factors of culture, social, personal and psychological all together have significant effect to the consumer purchase decision of online fresh fish purchase behavior. However social factors do not have direct effect to the consumer purchase decision of online fresh fish purchase behavior. Keywords: Fresh Fish, Consumer Behavior, Purchase Decision, New Normal.